Remembering "the father of the contemporary state of Croatia" - Belaj, Marijana (Traditiones (Ljubljana), 2014)
This article explores diverse strategies and mechanisms of remembering Franjo Tuđman, Croatia's first president, after the country gained its independence in 1991. The authors discuss how Tuđman's figure is constructed in contemporary Croatian society by focusing on its use in political discourse and in public space. The article's central part deals with realms of memory in Veliko Trgovišće, Tuđman's birthplace, on the ninety-second anniversary of his birth.
Keywords: cultural anthropology; Tuđman, Franjo, 1922-1999; history; kulturna antropologija; personalities; zgodovina; politics; osebnosti; Croatia; voditelji; politika; postsocializem; Hrvaška